The expected and perceived well-being effects of short-term self-tracking technology use. (2017) - Kari, Tuomas; Koivunen, Sanna; Frank, Lauri; Makkonen, Markus; Moilanen, Panu
Individuals and the healthcare sector have become increasingly interested to measure and improve health and well-being by using different self-tracking technologies. Physical activity, nutrition, and sleep are a few of the various measures that can be self-tracked by different technological solutions. This study investigates the expected and perceived well-being effects of short-term self-tracking technology use with focus on the implementation phase. The study is based on thematic analysis of ten semi-structured interviews. The results reveal that the perceived well-being effects of using a self-tracking technology are relatively minor during the implementation phase - in line with the pre-implementation expectations. The possible increase in well-being is expected to occur in a longer time scale. Perceived psychological well-being is found to be affected the most during the implementation phase. The results also reveal interesting findings regarding the use and acceptance of self-tracking technologies. Based on the results, theoretical and practical implications are presented.